1995
DOI: 10.1007/bf00193738
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens-mediated transformation of broccoli (Brassica oleracea var. italica) and cabbage (B. oleracea var. capitata)

Abstract: Transgenic broccoli (Brassica oleracea var. italica) was produced by two Agrobacterium tumefaciens-mediated transformation methods. One used flowering stalk explants from mature plants; the other used hypocotyl and petiole explants from in vitro-grown seedlings. Several hundred transformants containing a Bacillus thuringiensis ∂-endotoxin gene (CryIA(c)-type) and the neomycin phosphotransferase gene were recovered. Rooted transformants were obtained in as little as 3 months using seedling explants. Transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 24 publications
2
52
0
3
Order By: Relevance
“…The protocol reported here is efficient and reliable. Just like other Brassica species (Mathews et al, 1990;Metz et al, 1995;Cao and Earle, 2003; Wahlroos et al, 2003), which were reported in successful genetic transformation, this protocol may be useful in genetic improvement by using transgenic approach because this crop is suffering a severe virus infection in China.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The protocol reported here is efficient and reliable. Just like other Brassica species (Mathews et al, 1990;Metz et al, 1995;Cao and Earle, 2003; Wahlroos et al, 2003), which were reported in successful genetic transformation, this protocol may be useful in genetic improvement by using transgenic approach because this crop is suffering a severe virus infection in China.…”
mentioning
confidence: 87%
“…Stem mustard is a swelling stem vegetable widely grown in the Changjiang River valley, especially in Shichuan and Zhejiang provinces of China, but is not well known in other countries (Guo et al, 1994). Successful in vitro culture, regeneration, propagation and transformation from other Brassica species have been reported (Mathews et al, 1985(Mathews et al, , 1990Metz et al, 1995;Eapen and George, 1997;Cao and Earle, 2003;Wahlroos et al, 2003). However, a systematic study of in vitro culture of stem mustard is lack.…”
mentioning
confidence: 99%
“…Two types of broccoli (Brassica oleracea L.) were used in this study. The Þrst produced high levels of Cry1Ac (Metz et al 1995b) and expression was veriÞed by screening 4 Ð5-wk-old plants with susceptible P. xylostella neonates (Tang et al 2001). The plants on which neonates showed 0% survival were used in the tests.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this method is readily adopted for plant genetic engineering. Transformation using Agrobacterium has become common in horticultural plants such as in lettuce (Michelmore et al, 1987), cabbage (Metz et al, 1995;Jin et al, 2000;Lee et al, 2000), kale (Cogan et al, 2001), orchids (Semiarti et al, 2007 and2010;Chin and Mii, 2011), and petunias (Klee et al, 1987). With genes that can modulate auxin concentrations, transgenic techniques have been used to manipulate endogenous levels of auxin in plants.…”
Section: Modern Breeding Through Biotechnologymentioning
confidence: 99%